Refining Adab, Love, And Tolerance In Islamic Pedagogy - Jasminto, Jasminto (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2025)
This study is a comparative literature review of two monumental works titled Adabul ‘Ālim wal Muta‘allim, authored respectively by Imam Nawawi and KH. Hasyim Asy’ari. Both texts encapsulate a rich legacy of scholarly ethics and the spiritual foundations of Islamic education, particularly in shaping students and educators of noble character, deep love for knowledge, and a strong commitment to tolerance and humanity. Employing a philosophical approach to Islamic education and content analysis, this research aims to explore the convergence and distinctions between Imam Nawawi—representing global Islamic scholarship—and KH. Hasyim Asy’ari—embodying local wisdom from the Indonesian pesantren tradition. The findings reveal that despite differing socio-historical contexts, both scholars share a unified vision of education that elevates adab (ethics) as a prerequisite for knowledge, love as the basis for learning, and tolerance as the path toward harmony. This study highlights that integrating global scholarly heritage with local wisdom offers a powerful paradigm for developing a humanistic Islamic education that contributes to global peace and inter-civilizational dialogue.